ML290 is a biased allosteric agonist at the relaxin receptor RXFP1 - Martina Kocan (Nature Portfolio, 2017)
Abstract Activation of the relaxin receptor RXFP1 has been associated with improved survival in acute heart failure. ML290 is a small molecule RXFP1 agonist with simple structure, long half-life and high stability. Here we demonstrate that ML290 is a biased agonist in human cells expressing RXFP1 with long-term beneficial actions on markers of fibrosis in human cardiac fibroblasts (HCFs). ML290 did not directly compete with orthosteric relaxin binding and did not affect binding kinetics, but did increase binding to RXFP1. In HEK-RXFP1 cells, ML290 stimulated cAMP accumulation and p38MAPK phosphorylation but not cGMP accumulation or ERK1/2 phosphorylation although prior addition of ML290 increased p-ERK1/2 responses to relaxin. In human primary vascular endothelial and smooth muscle cells that endogenously express RXFP1, ML290 increased both cAMP and cGMP accumulation but not p-ERK1/2. In HCFs, ML290 increased cGMP accumulation but did not affect p-ERK1/2 and given chronically activated MMP-2 expression and inhibited TGF-β1-induced Smad2 and Smad3 phosphorylation. In vascular cells, ML290 was 10x more potent for cGMP accumulation and p-p38MAPK than for cAMP accumulation. ML290 caused strong coupling of RXFP1 to Gαs and GαoB but weak coupling to Gαi3. ML290 exhibited signalling bias at RXFP1 possessing a signalling profile indicative of vasodilator and anti-fibrotic properties.